ETHNIC COMPLEX «COSSACK STAN» ON THE TERRITORY OF KMV AS A TOPICAL COMPONENT OF TOURIST CLUSTER - I. V. Chubenko (Современная наука и инновации, 2022)
The development of Cossacks, which had a huge impact on the formation of cultural education, is very important. Cossacks are an integral part of the history of the region. In the Stavropol region, the Cossack classes and schools are being opened more often, in which a younger generation is brought up, respecting the older and honoring Orthodoxy, which underlies cultural education. In order that everyone can plunge into the cossack way of life, you need to create places where it will be available to everyone.